2023
DOI: 10.7717/peerj.15509
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ and CD8+ cell counts are significantly correlated with absolute lymphocyte count in hospitalized COVID-19 patients: a retrospective study

Phey Liana,
Aprilia Paskah Samosir,
Nurmalia Purnama Sari
et al.

Abstract: Background Coronavirus disease 2019 (COVID-19) is a contagious respiratory illness that was declared a pandemic in March 2020. Lymphopenia is one of the specific laboratory results disturbance in COVID-19 patients. Such findings are frequently associated with substantial changes in T-cell counts, particularly CD4+ and CD8+ T-cells. This study aimed to examine the correlation between CD4+ and CD8+ cell counts and absolute lymphocyte count (ALC) in COVID-19 patients and analyze its difference based on the COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Similar findings have been reported by other authors, who have demonstrated that low numbers of CD4+, CD8+, and CD19+ T lymphocytes are associated with a higher risk of death. The number of CD4+ T lymphocytes is currently considered an important prognostic marker of survival [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been reported by other authors, who have demonstrated that low numbers of CD4+, CD8+, and CD19+ T lymphocytes are associated with a higher risk of death. The number of CD4+ T lymphocytes is currently considered an important prognostic marker of survival [31][32][33].…”
Section: Discussionmentioning
confidence: 99%